If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + 10x = 72 + 2x Solving 24 + 10x = 72 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 24 + 10x + -2x = 72 + 2x + -2x Combine like terms: 10x + -2x = 8x 24 + 8x = 72 + 2x + -2x Combine like terms: 2x + -2x = 0 24 + 8x = 72 + 0 24 + 8x = 72 Add '-24' to each side of the equation. 24 + -24 + 8x = 72 + -24 Combine like terms: 24 + -24 = 0 0 + 8x = 72 + -24 8x = 72 + -24 Combine like terms: 72 + -24 = 48 8x = 48 Divide each side by '8'. x = 6 Simplifying x = 6
| 7x+9=8x+7 | | 12+8x=4+10x | | 52+14x=104+1x | | 4x+36=13x+4 | | 1x+80=11x+70 | | 64+5x=16+13x | | 12+7x=9x+6 | | 14+11x=28+4x | | 4x+88=15x+44 | | 40+7x=15x+24 | | 3x+72=9+12x | | 4s+31=95 | | 7x+14=7+14x | | 2x+56=7+9x | | 42+3x=10x+7 | | 2x+48=36+8x | | 90+2x=70+12x | | 25+3x=8x+20 | | 91+15x=104+2x | | 36+12x=72+3x | | 12+4x=7x+3 | | 3+7x=12+4x | | 8x+27=24+11x | | 12+12x=6x+30 | | 8+12x=28+8x | | 28+7x=14x+21 | | 10+11x=45+6x | | 2x+66=55+13x | | 14x+25=9x+40 | | 5p+4q=46 | | 36+3x=30+9x | | 18+7x=12+10x |